Houses of hide and earth : native dwellings : Plains Indians - Shemie, Bonnie (Montreal, Quebec ; Plattsburgh, N.Y. : Tundra Books, 1991)
Describes the materials, construction, and uses of the tipis and earthlodges used by the Plains Indians.
Keywords: Indians of North America -- Great Plains; Indians of North America